Two photon excitable graphene quantum dots for structured illumination microscopy and imaging applications: lysosome specificity and tissue-dependent imaging. Issue 4 (17th December 2018) - Singh, Harwinder; Sreedharan, Sreejesh; Tiwari, Karishma; Green, Nicola H.; Smythe, Carl; Pramanik, Sumit Kumar; Thomas, Jim A.; Das, Amitava
Abstract : Two-photon active graphene quantum dots (GQDs) are obtained from extracts of the neem root. Abstract : Biocompatible graphene quantum dots (GQDs), obtained from extracts of neem root, are found to be suitable for structured illumination microscopy and two-photon microscopy (TPM). Results of TPM and confocal luminescence microscopy ensure lysosome specificity in live cells and tissue-dependent localization in zebrafish, respectively, of GQDs.